ln(x-3)+ln(x-4)=ln(x+1)

Simple and best practice solution for ln(x-3)+ln(x-4)=ln(x+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for ln(x-3)+ln(x-4)=ln(x+1) equation:


Simplifying
ln(x + -3) + ln(x + -4) = ln(x + 1)

Reorder the terms:
ln(-3 + x) + ln(x + -4) = ln(x + 1)
(-3 * ln + x * ln) + ln(x + -4) = ln(x + 1)
(-3ln + lnx) + ln(x + -4) = ln(x + 1)

Reorder the terms:
-3ln + lnx + ln(-4 + x) = ln(x + 1)
-3ln + lnx + (-4 * ln + x * ln) = ln(x + 1)
-3ln + lnx + (-4ln + lnx) = ln(x + 1)

Reorder the terms:
-3ln + -4ln + lnx + lnx = ln(x + 1)

Combine like terms: -3ln + -4ln = -7ln
-7ln + lnx + lnx = ln(x + 1)

Combine like terms: lnx + lnx = 2lnx
-7ln + 2lnx = ln(x + 1)

Reorder the terms:
-7ln + 2lnx = ln(1 + x)
-7ln + 2lnx = (1 * ln + x * ln)
-7ln + 2lnx = (1ln + lnx)

Solving
-7ln + 2lnx = 1ln + lnx

Solving for variable 'l'.

Move all terms containing l to the left, all other terms to the right.

Add '-1ln' to each side of the equation.
-7ln + -1ln + 2lnx = 1ln + -1ln + lnx

Combine like terms: -7ln + -1ln = -8ln
-8ln + 2lnx = 1ln + -1ln + lnx

Combine like terms: 1ln + -1ln = 0
-8ln + 2lnx = 0 + lnx
-8ln + 2lnx = lnx

Add '-1lnx' to each side of the equation.
-8ln + 2lnx + -1lnx = lnx + -1lnx

Combine like terms: 2lnx + -1lnx = 1lnx
-8ln + 1lnx = lnx + -1lnx

Combine like terms: lnx + -1lnx = 0
-8ln + 1lnx = 0

Factor out the Greatest Common Factor (GCF), 'ln'.
ln(-8 + x) = 0

Subproblem 1

Set the factor 'ln' equal to zero and attempt to solve: Simplifying ln = 0 Solving ln = 0 Move all terms containing l to the left, all other terms to the right. Simplifying ln = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.

Subproblem 2

Set the factor '(-8 + x)' equal to zero and attempt to solve: Simplifying -8 + x = 0 Solving -8 + x = 0 Move all terms containing l to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + x = 0 + 8 Combine like terms: -8 + 8 = 0 0 + x = 0 + 8 x = 0 + 8 Combine like terms: 0 + 8 = 8 x = 8 Add '-1x' to each side of the equation. x + -1x = 8 + -1x Combine like terms: x + -1x = 0 0 = 8 + -1x Simplifying 0 = 8 + -1x The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.

See similar equations:

| 3n^2+-53=10n | | y=17x^2-21 | | 7-(2n-9)=3-3n | | -3.2x+14.08=-4.8 | | 3x+4-5x=10x+5 | | y^3+8y^2-23y-210=0 | | -3/10=x-5/8 | | 125=-5(3+x) | | 2x+3=5x-3 | | S=4k+4w | | -3(x-2)=16 | | t^2-2t-120=0 | | 3x+x=130 | | 3(n+5)+2=60 | | 4w-6= | | .20*40= | | n^2=6n+72 | | b/4+5=14 | | x+y=130 | | a/9=6 | | -7=11+x | | 2x-5x=-6 | | 3*76= | | (9x-81)=12 | | 34/6=2x+1/3 | | 3x^2-2x-12x+8= | | 3x+y=130 | | 6y=30y+140 | | 2abc+d=3 | | -5y-2y+3y=9 | | -19-(-4)=x | | -10-(-5)=x |

Equations solver categories